Sequelas pulmonares da COVID-19 após recuperação em pacientes críticos: avaliação clínica, radiológica e funcional pulmonar - Laura Braga de Sousa (2022)
Objective: Describe the pulmonary sequelae of severe COVID-2019 three months after cure. Design: In a prospective cohort study, survivors of COVID-19 who had been admitted to intensive care were assessed in consultation, 3 months after cure, through a validated questionnaire - Severe Respiratory Insufficiency, through a thorax CT scan, and through pulmonary function tests. Setting: Patients admitted to Infectious Diseases Intensive Care Unit of a tertiary Hospital (São João Hospital, Porto, Portugal) discharged alive were invited to be assessed, three months after cure. Patients or participants: Survivors of severe COVID-19 from March to December 2020. Interventions: There are no interventions Main variables of interest: Severe Respiratory Insufficiency-Portuguese score, chest CT scan sequelae, and pulmonary function tests. Results: 58% of the patients had at least one abnormality on the CT-scan. The presence of an active cancer and a lengthier hospitalization were positively associated with the development of chest CT-scan sequelae. Respiratory function tests showed mainly a deficit in the diffusing capacity for carbon monoxide. Clinically, the domain most affected was attendant symptoms and sleep. Females, older patients, and those with comorbidities had lower SRI-PT scores. Conclusions: Most of the patients had chest CT-scan sequelae 3 months after discharge, but a minority had abnormalities in respiratory function tests. The presence of active cancer and a lengthier hospitalization are risk factors to lung sequelae in chest CT-scan. Age, female sex, and comorbidities are risk factors for the permanence of symptomatic sequelae. Patients with severe COVID-19 disease need post-discharge care.